Potensi Ancaman dan Upaya Mitigasi Emisi Gas Rumah Kaca di Sektor Pertanian Indonesia : Tinjauan Sistematis atas Literatur - Ngadisih, Ngadisih; Sinatrya, Azka; Retno Wulan, Indah; Claudea Tanjung, Jeane; Fahima, Sahidatun; Lestari, Prieskarinda (Universitas Tanjungpura, 2024)
Agriculture in Indonesia is a vital sector that can fulfill food needs and provide livelihoods. However, agriculture also contributes to greenhouse gas (GHG) emissions. Indonesia's agricultural sector contributes around 14% of emissions globally and 7% nationally. Greenhouse gas emissions such as methane gas CH4, carbon dioxide CO2, and nitrous oxide N2O are generated from agricultural activities ranging from land preparation, fertilization, transportation of agricultural products, to processing in factories. These greenhouse gas emissions influence the climate change that occurs and affect the increase in temperature and rainfall patterns. In mitigation efforts, this study noted several steps taken. Energy conversion, such as the use of biogas from animal manure can reduce CH4 emissions and the use of pellets from palm waste processing can reduce CO2 emissions. Reforestation with special carbon-absorbing plants to reduce CO2 emissions. The use of organic fertilizers as a partial replacement for inorganic fertilizers is useful in reducing CH4 and N2O emissions. Through this systematic review, it is expected to contribute to the understanding of the role of the agricultural sector in greenhouse gas emissions in Indonesia and provide insight into mitigation efforts that can be applied in achieving sustainable agriculture.